Combination of cardanol-derived flame retardant with SiO2@MOF particles for simultaneously enhancing the toughness, anti-flammability and smoke suppression of epoxy thermosets. (October 2021) - Huang, Jiali; Guo, Wenwen; Wang, Xin; Niu, Haoxin; Song, Lei; Hu, Yuan
Abstract: In this work, an organic-inorganic flame retardant composite system was utilized by combining the renewable cardanol-based flame-retardant toughening agent (CF-PO(OPh)2 ) and the core-shell SiO2 @MOF particles, then a series of high-performance epoxy composites with simultaneously enhanced mechanical properties, fire safety as well as smoke suppression effect were prepared with incorporating different ratio of the organic and inorganic flame retardant components. The epoxy composite containing 3% CF-PO(OPh)2 and 2% SiO2 @UiO-66 (EP3) showed the most striking enhancements in the mechanical and flame retardant performances. The tensile strength and impact strength of EP3 was 48.8% and 25.3% higher than those of EP0, respectively. In view of flame retardant properties, EP3 showed maximum reductions in PHRR, SPR, CO, and CO2 productions which were 30.5%, 25.8%, 51.4%, and 43.7% lower than those of EP0, respectively. The excellent flame retardant and mechanical properties of epoxy composites resulted from the synergetic effect of cardanol-based phosphorus-containing CF-PO(OPh)2 and inorganic core-shell SiO2 @UiO-66 particles. Graphical abstract: Image 1 Highlights: EP composites showed simultaneously enhanced toughness, anti-flammability and smoke suppression. The tensile strength and impact strength of EP3 were 48.8% and 25.3% higher than those of EP0, respectively. EP3 showed maximum reductions in PHRR, SPR, CO, and CO2 production as compared to those of EP0.